2000
DOI: 10.1258/rsmacta.41.1.89
|View full text |Cite
|
Sign up to set email alerts
|

MR findings of desmoplastic fibroma of the spine: A case report

Abstract: We report on the MR imaging findings in a case of spinal desmoplastic fibroma (DF). DF of the bone is a rare, locally aggressive tumor. It is commonly located in long bones, pelvis or mandible. DF involving the spine is extremely rare and difficult to distinguish from other bony lesions such as giant cell tumor, chordoma and fibrous dysplasia of the spine. This case of DF of the spine showed MR findings similar to those of DF arising in the metaphysis of a long bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The spinal location is extremely rare and only a few cases have been previously reported in the literature. Most of them were located in the thoracic or lumbar level [4,6,7,[9][10][11]. Our patient is the second case in the literature with desmoplastic fibroma of the cervical spine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The spinal location is extremely rare and only a few cases have been previously reported in the literature. Most of them were located in the thoracic or lumbar level [4,6,7,[9][10][11]. Our patient is the second case in the literature with desmoplastic fibroma of the cervical spine.…”
Section: Discussionmentioning
confidence: 95%
“…The magnetic resonance imaging of this tumor is useful in determining the presence of spinal cord compression. Kong et al [6] reported a case of lumbar spinal desmoplastic fibroma, and mentioned the MRI features of this rare tumor. In their case, a 24-year-old male patient presented with low back pain radiating to both Desmoplastic fibroma is a locally aggressive tumor with a 20-30% recurrence rate reported; therefore, complete excision is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…13 Diagnostic confirmation requires histological examination. On microscopic and pathological analysis the lesions are a gray-white color and composed of spindle cells on a richly collagenous and variably hyalinized background; the differential diagnosis should include more common spindle-cell tumors and primary bone tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients most commonly present in the 2nd or 3rd decades of life without gender bias, 28 with disease appearing in the long tubular bones, such as the femur and humerus, and very rarely in the pelvis, skull, or spine. 5 To our knowledge, there have been only 4 reports of DF involving the cervical spine, 1,7,28,30 5 cases of thoracic DF, 9,12,15,21,27 2 cases of lumbar DF, 13,25 and 2 cases of sacral DF 24,31 (Table 1). Instead of discussing slow-growing DFs, as have been presented in past case reports, we describe 2 cases of aggressive DF of the cervicothoracic spine encasing the brachial plexus and causing significant mediastinal compression.…”
mentioning
confidence: 99%
See 1 more Smart Citation